Opioids and Vitamin C: Known Interactions and Potential for Redox-Signaling Crosstalk - Mackenzie Newman; Heather Connery; Jonathan Boyd (MDPI AG, 2022)
Opioids are among the most widely used classes of pharmacologically active compounds both clinically and recreationally. Beyond their analgesic efficacy via μ opioid receptor (MOR) agonism, a prominent side effect is central respiratory depression, leading to systemic hypoxia and free radical generation. Vitamin C (ascorbic acid; AA) is an essential antioxidant vitamin and is involved in the recycling of redox cofactors associated with inflammation. While AA has been shown to reduce some of the negative side effects of opioids, the underlying mechanisms have not been explored. The present review seeks to provide a signaling framework under which MOR activation and AA may interact. AA can directly quench reactive oxygen and nitrogen species induced by opioids, yet this activity alone does not sufficiently describe observations. Downstream of MOR activation, confounding effects from AA with STAT3, HIF1α, and NF-κB have the potential to block production of antioxidant proteins such as nitric oxide synthase and superoxide dismutase. Further mechanistic research is necessary to understand the underlying signaling crosstalk of MOR activation and AA in the amelioration of the negative, potentially fatal side effects of opioids.